Gender differences in description of chronic musculoskeletal pain - Siwach, Priyanka; Verma, Bhawna; Gakhar , Megha (International Journal of Research in Medical Sciences, 2023)
Background: Pain is a subjective experience and different people describe their pain differently. Due to biological, psychological and sociocultural differences among different gender there is a variation in their pain experiences. Though gender differences in medical history taking have been studied it is still a concept that needs exploration. In addition the gender differences in the impact of pain on sleep function needs to be explored. Methods: A sample of 240 patients including both male and females were randomly recruited from OPD of a tertiary care hospital. The patients were asked to describe their pain in terms of quality through face to face structured interview. The number of descriptors used by every individual was noted. Specific questions regarding pain intensity on numeric pain rating scale and sleep function were also recorded. Results: 67.8% of females used more than two descriptors to explain their pain compared to 53.3% of males. The mean pain intensity reported by females was 7.28±1.24 which was significantly higher than males. 37.8% of females reported bad sleep quality as compared to 16.7% of males. Conclusions: Females report greater pain intensity and use more number of descriptors to report their pain. In addition there is higher impact of musculoskeletal pain on sleep quality in females than in males.